HUBUNGAN PMBA, PENGETAHUAN GIZI, ASUPAN MAKAN DAN STATUS PENYAKIT INFEKSI DENGAN STATUS GIZI BALITA - Mohammad Furqan; Ahmad Faridi; Alib Birwin; Eka Susanti; Rafly zar (Poltekkes Kemenkes Semarang, 2020)
Background: Nutritional status is fully determined by the nutrients the body needs and other factors that determine the amount of absorption and use of these substances.Objective: in this study to determine the relationship between infant and toddler feeding patterns, nutritional knowledge, infection status and food intake with the nutritional status of children under five in Pagelaran Village, Pandeglang.Method: The study design was cross sectional with all toddlers as respondents, aged 0 - 59 months.Result: Feeding patterns of infants and children (PMBA) with the same nutritional status as thin, thin and obese in providing food is still not right, namely 72.7 with no significant relationship where the p-value 0.05. Meanwhile, maternal nutrition knowledge, infectious disease status and food intake related to energy intake all did not have a significant relationship where the p-value was 0.05.Conclusion: The pattern of feeding infants and children by mothers is still not as expected, where the level of mother's knowledge is still low about how to feed babies and children (PMBA).